Bullous pemphigoid: a case report - Simões, Isabel Maria Gama (2018)
Introduction: Bullous pemphigoid is the most common autoimmune bullous dermatosis in Western Europe. It is a chronic disease with spontaneous remissions and exacerbations and, consequently, significant morbidity. Case description: 77-year-old male patient, from a low-middle class nuclear family, with a history of type 2 diabetes mellitus, hypertension, obesity, and benign prostatic hyperplasia. The patient was observed at the emergency department due to an itchy rash on the upper limbs evolving over 10 days, which further generalised to the trunk and lower limbs, and without improvement despite previous treatment with bilastine. The therapeutic prescribed included flucloxacillin, ciprofloxacin, deflazacort, hydroxyzine hydrochloride and topic emollient, and the patient was discharged and referred to Dermatology. At the Dermatology appointment, the patient exhibited bullous lesions with serohematic content on erythematous plaques in the inguinal region and lower limbs, with negative Nikolsky’s sign. Confluent urticarial lesions were observed in the upper limbs and trunk, as well as crustal lesions in the flexor regions of the upper limbs. Based on the diagnostic hypothesis of bullous pemphigoid, a biopsy of a blister was performed, and prior therapy was suspended and replaced by oral prednisolone, topical betamethasone, topical fusidic acid, oral ranitidine, diet, glucose monitoring, and laboratory analysis. At follow-up, the patient did not exhibit de novo lesions, and the dose of prednisolone was gradually reduced. Histological examination confirmed the diagnosis of bullous pemphigoid. Commentary: Early diagnosis of bullous pemphigoid is crucial and family physicians hold a privileged position for its initial management and timely referral.